Enhancing adaptive performance in emergency response: Empowerment practices and the moderating role of tempo balance. (February 2021) - Huntsman, David; Greer, Alex; Murphy, Haley; Haynes, Steven
Highlights: Empowerment practices buffer hierarchical constraints during complex emergencies. Development, autonomy, and voice with senior leaders enhance adaptive performance. Balanced workloads help firefighters become more resilient in complex emergencies. Access to development and autonomy is most important under poor tempo balance levels. Abstract: Fire departments, like other organizations that follow rigid hierarchical structures, face difficulties in being flexible or adaptive enough to address the needs generated by large and complex disaster environments. Research is lacking, however, on the ability of empowerment practices to enhance adaptive performance in emergency response organizations, which today face increasingly complex threats and growing responsibilities. The present study explores the relationships between the empowerment practices of career development opportunities, work autonomy, employee voice with two leadership levels, and department adaptive performance. Moreover, tempo balance and the empowerment practices are tested for interactive effects, a measure we developed to capture firefighter stress and fatigue from excessive mandatory overtime policies. Data were collected from 756 United States firefighters located on the west coast. The results show that the empowerment practices enhance adaptive performance by helping firefighters respond to unpredictable aspects of their work environment. In addition, tempo balance moderates career development opportunities, work autonomy, and adaptive performance, specifically. The findings show that firefighters are better able to overcome stress and fatigue during complex incidents by relying on their training and ability to improvise, meaning these empowerment practices help compensate for poor tempo balance in fire departments from ineffective scheduling.